A study of methods of applying granulated systemics to control plant lice in wheat - Fehn, Licelma Martins (Pesquisa Agropecuaria Brasileira, 2014)
In 1968 a field experiment was conducted using wheat treated with granulated systemic insecticides. The application methods studied were depth of application, furrow placing, and side banding at the time of planting. The principal objective was to determine the duration of toxicity in the plant with relation to attack by plant lice and Homopteros and the effect on yields. It was demonstrated that efficient protection was available for 65 days after germination. It was also shown, by the relatively high yields and the presence of virus symptoms on all plots including tests plots, that protection was against insects and not virus diseases. No plant toxicity was observed in the wheat that could be attributed to the introduction of toxins through the bites of plant lice. The relation of treatment cost to yields proved advantage in using insecticides under the conditions of the experiment.